The asylum-integration paradox: comparing asylum support systems and refugee integration in the Netherlands and the UK - Bakker, Linda (International migration, 2016)
This article explores the impact of asylum support systems on refugee integration focusing on the UK and the Netherlands. Both have adopted deterrent approaches to asylum support. The Dutch favour the use of asylum accommodation centres, segregating asylum seekers from the general population. The UK disperses asylum seekers to housing within deprived areas, embedding them within communities. Both countries have been criticized for these practices, which are viewed as potentially anti-integrative: something of a paradox given that both promote the importance of refugee integration. We analyse national refugee integration surveys in both countries and provide original empirical evidence of negative associations between asylum support systems and refugees' health, which differ in relation to mental and physical health. The integration and asylum policy implications of these findings are discussed.